Strategi Membangun UMKM Unggul Dengan Paningkatan Kemampuan Pemasaran dan Inovasi Kemasan Melalui Digital Marketing di Desa Cibuntu - Teliana, Nala; Suhendra, Suhendra; Ramadini, Gadis Aulia; Muhammad Agil Ghifari, Muhammad Agil Ghifari; Nurhanifah, Nurhanifah; Saputra, Rizqi Maulana (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
This study aims to determine the potential, shortcomings, and appropriate strategies to improve marketing capabilities and packaging innovation which was held with workshops with residents of Cibuntu Village, Wanayasa District, who have MSMEs. This research uses qualitative methods by taking data aware of observation, interviews, documentation, and holding a Group Discussion Forum (FGD).  The results of this study show that the disadvantages of 15 MSMEs in Cibuntu Village include capital problems, local marketing, packaging innovation, and lack of branding on social media. With the problems experienced by MSME actors in Cibuntu Village, researchers held an MSME Workshop held by researchers, namely "W-Fest UMKM Go Digital".  In this workshop, MSME players were given material on marketing on social media, product branding on social media, packaging innovation, understanding business features on Instagram, having a business account on Instagram, and knowing sales methods in e-commerce. In addition, researchers and the community also created a group consisting of MSME actors in Cibuntu Village as a forum or means to coordinate and facilitate MSME players to share experiences and the latest innovations from their products.